2019
DOI: 10.1039/c9ra05163e
|View full text |Cite
|
Sign up to set email alerts
|

Glycine betaine enhances biodegradation of phenol in high saline environments by the halophilic strainOceanobacillussp. PT-20

Abstract: The halophilic bacterial strain PT-20, isolated from saline alkali soil samples and identified as a member of the genus Oceanobacillus, exhibited a robust ability to degrade phenol under high salt conditions. It was determined that strain PT-20 was capable of degrading 1000 mg L À1 phenol completely in the presence of 10% NaCl within 120 h. Under the optimal degradation conditions, pH 8.0, 3% NaCl and 30 C, 1000 mg L À1 phenol could be completely degraded in 48 h. Interestingly, the biodegradation rate of phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…At neutral or slightly alkaline environment, the degraded efficiency is high, especially at pH 9. Compared with the reported strains (Wu et al 2018;Long et al 2019;Lee et al 2020), the degraded pH range of strain ZWB3 is wider, which can better adapt to the change of acid and alkali environment, while the degradation efficiency under neutral and slightly alkaline conditions is better. The reason is that phenol is transformed to organic acids through ring opening in the process of microbial degradation, which leads to the decrease of pH in the environment.…”
Section: The Influences On Phenol Biodegradationmentioning
confidence: 86%
See 1 more Smart Citation
“…At neutral or slightly alkaline environment, the degraded efficiency is high, especially at pH 9. Compared with the reported strains (Wu et al 2018;Long et al 2019;Lee et al 2020), the degraded pH range of strain ZWB3 is wider, which can better adapt to the change of acid and alkali environment, while the degradation efficiency under neutral and slightly alkaline conditions is better. The reason is that phenol is transformed to organic acids through ring opening in the process of microbial degradation, which leads to the decrease of pH in the environment.…”
Section: The Influences On Phenol Biodegradationmentioning
confidence: 86%
“…In addition to phenol, the industrial wastewater often contains phenol derivatives and heavy metal ions, which bring great challenge for efficient biodegradation associated with tolerance of microorganisms in the harsh environment. At present, most microbial degradation of phenol concentration range of about 1,000-1,200 mg/L, and the time required for complete degradation ranges from about 32-75 h (Shahryari et al 2018; Gomes e Silva et al 2019;Long et al 2019;Nouri et al 2020;Wen et al 2020;Gong et al 2021). Therefore, many known phenol degrading microorganisms still have limitations in biodegradation ability and rate.…”
Section: Introductionmentioning
confidence: 99%
“…Under 10% NaCl, PT-20 completely degrades 1000 mg�L -1 phenol within 120 h. After adding GB, the time was shortened to 72 h, and the corresponding average degradation rate was increased from 8.43 to 14.28 mg�L -1 �h -1 . The results of transcriptome analysis showed that the addition of GB enhanced the resistance of cells to phenol; furthermore, GB increased the growth rate of strain PT-20 and up-regulated the expression of related enzyme genes [20]. Although researchers have conducted many studies on the effect of exogenous GB on plant responses to stress, there have been few transcriptome studies aimed at revealing the mechanism by which GB mitigates the effects of salt stress in maize.…”
Section: Introductionmentioning
confidence: 99%